Management of Zakat Payment Based on Fintech for the Good Corporate Governance Improvement - Utami, Pertiwi; Basrowi; Julianas, dan (Eastern Journal of Economics and Finance, 2019)
The researcher conducted a study of Fintech-based zakat payment legal knowledge at the National Zakat Amil Agency (BAZNAS) in Indonesia. This research basically addresses two main points. First, about how the 'aqeedah' and 'sharia' knowledge approaches to the use of Finech-based zakat payments. Second, about how to implement the principles of good corporate governance in the management of Fintech-based payment zakat. Using an explorative methodology, researchers want to provide new insights in terms of legal studies with both approaches. From the results of analysis and discussion, revealed that Fintech's law itself is permitted, not binding because the contract is in the same direction, and as long as it does not conflict with sharia principles and does not contain elements of harm. While the implementation of the principles of zakat payment based on Fintech was able to create good corporate governance in BAZNAS quite well.